Ketidakadilan Gender terhadap Perempuan dalam Novel Layangan Putus Karya Mommy ASF - Wicaksono, Andri; Wati, Kadek Dwi Irna; Alfiawati, Riska (Journal of Feminism and Gender Studies, 2022)
This research on gender injustice in the novel Layangan Putus by Mommy ASF examines gender injustice against women in the novel. The purpose of this study is to describe and obtain an overview of gender injustice against women in the novel Layangan Putus by Mommy ASF through a feminist approach. The forms of gender inequality are: 1) Marginalization of women, 2) Subordination of women, 3) Stereotypes against women, 4) Violence against women. This research is expected to help increase the treasury of studies on literature, especially on the issue of gender inequality in literary works in Indonesia. This study uses a literary approach based on gender inequality by using a feminist approach. The object of this research is the novel Layangan Putus by Mommy ASF. This study uses a descriptive qualitative method that involves the researcher directly in the entire process, the research starts from problem determination, literature review, data collection and processing, analysis and interpretation processes to the conclusion of the study. The results show a picture of gender injustice experienced by female characters by the husbands of female characters in the novel Layangan Putus, in this study there are four forms of gender injustice against women, namely marginalization of women, subordination of women, stereotypes against women and violence against women. and the most experienced gender injustice in the novel Layangan Putus is the subordination of women.